Kopplung, Steuerung, Differenzierung - zur Geographie sozialer Systeme - Lippuner, Roland (ERDKUNDE, 2007)
German-speaking geography has responded to the recently proclaimed turns in thinking in the social sciences and humanities – the so-called cultural and spatial turns – with a redoubled search for new theoretical approaches. In the course of this search, NIKLAS LUHMANN’s theory of social systems, among others, has attracted much interest. Although the concept of space plays only a peripheral role in LUHMANN’s theory, systems theory opens up a range of possibilities for engaging with the ‘geography of social systems’. This essay begins with a discussion of the role of space in LUHMANN’s theory. Against this background a systems-theoretic conception of relations between system and environment is discussed. The subsequent section then takes up communication-theoretic arguments regarding the steering potential of spatial semantics. The third part develops some considerations for an engagement with the image of space that is produced and reproduced both in everyday and in scholarly observations and descriptions of (apparently aspatial) social systems. The different perspectives emerging from a systems-theoretic encounter with ‘questions of space’ are investigated with an eye to their (implicit) spatial concepts and to their potential relevance to various problematics within specific fields of human geography. It is argued that the thematization of spatial arrangement emerging from the version of systems theory focused on articulations between system and environment takes up lines of argument from classical or traditional geography. The communications-theoretic analysis of the construction of space (‘spatial semantics’) could, by contrast, inform new approaches within cultural geography (or critical geopolitics). Finally, theoretical considerations regarding space as an indispensable schematic element of observations dependent upon differentiation point beyond the current self-understanding of academic geography. With this conceptual architecture a systems-theoretic social geography would be able to describe relations in the social world as a ‘geography of social systems’.